THE PRINCIPLE OF JUSTICE TOWARD THE WTO RETALIATION BASED ON ARTICLE 22 OF DISPUTE SETTLEMENT UNDERSTANDING - Wening Tiarashanny; IntanInayatun Soeparna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
World Trade Organization (WTO) as the only world trade organization. The principle of justice in international trade is not done as it should because there are still many cases of fraud from various kinds of state backgrounds, thus it is necessary to hold retaliation as a form of corrective justice in international trade law, which aims to rebalance trade. This studyaims to analyze the regulation of WTO international trade law based on the principle of justice, and analyze the fulfillment of the justice principle in implementing international trade retaliation which based on the provision of Article 22 Dispute Settlement Understanding (DSU). The type of study conducted was juridical-normative through the statute approach, case approach, historical approach, comparative approach and conceptual approach. Retaliation as a dispute resolution mechanism in the WTO did not work according to its objectives as specified in Article 3.3 of DSU. Based on the analysis,the legal regulation applied the first principle of justice to procedural aspects in each structure of the WTO, meanwhile the second principle of justice was applied to the substantial aspects from the implementation of international trade. In some cases, the fulfillment of the justice principle was fulfilled only in the retaliation conducted by Developed Countries and Developed Countries.